2013
DOI: 10.1038/leu.2013.336
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of genetic lesions in 944 patients with myelodysplastic syndromes

Abstract: High-throughput DNA sequencing significantly contributed to diagnosis and prognostication in patients with myelodysplastic syndromes (MDS). We determined the biological and prognostic significance of genetic aberrations in MDS. In total, 944 patients with various MDS subtypes were screened for known/putative mutations/deletions in 104 genes using targeted deep sequencing and array-based genomic hybridization. In total, 845/944 patients (89.5%) harbored at least one mutation (median, 3 per patient; range, 0–12)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

76
1,489
16
30

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,361 publications
(1,643 citation statements)
references
References 31 publications
76
1,489
16
30
Order By: Relevance
“…As previously reported we detected an increased number of genetic lesions in high‐risk WHO subtypes (Supporting Information Figure S3A) and found a correlation between the average number of genetic aberrations and the IPSS‐R prognostic risk score (Supporting Information Figure S3B) 1, 2. Interestingly, low risk patients displayed an increased number of somatic mutations compared to the number of lesions detected by CBA or SNP‐A.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…As previously reported we detected an increased number of genetic lesions in high‐risk WHO subtypes (Supporting Information Figure S3A) and found a correlation between the average number of genetic aberrations and the IPSS‐R prognostic risk score (Supporting Information Figure S3B) 1, 2. Interestingly, low risk patients displayed an increased number of somatic mutations compared to the number of lesions detected by CBA or SNP‐A.…”
supporting
confidence: 83%
“…To identify molecular markers of clinical relevance, we screened genes previously reported to be frequently mutated in MDS and other myeloid malignancies 1, 2. The somatic origin of the variants was validated by comparison of the concurrent samples (BMC, PB‐CD34, and PB‐MC) with a paired germline sample, peripheral CD3 + cells (PB‐CD3).…”
mentioning
confidence: 99%
“…Other MDS/AML-related genes were also recurrently mutated but at lower frequencies ( Figure 3). 18,20,66 The highly recurrent nature of well-characterized driver mutations indicates that they were selected by a Darwinian mechanism, rather than stochastically achieving a clonal dominance merely by a rapid expansion from a small number of residual stem cells ("bottleneck"). 9 In several patients, some of these genes, including PIGA, DNMT3A, ASXL1, BOCR, and RUNX1, harbor multiple, independent mutations, suggesting a strong selective pressure favoring evolution of cells having these mutations ( Figure 3A).…”
Section: Characteristics Of Mutations In Aamentioning
confidence: 99%
“…Previous studies on MDS patients showed that mutations in ASXL1, ETV6, EZH2, IDH2, RUNX1, and TP53 are predictors of poor overall survival in MDS patients independently of other established risk factors. [11][12][13] Furthermore the splicing machinery is one of the most frequently affected pathways in MDS, 14 and mutations in SRSF2 have been shown to be independently associated with a negative prognosis for overall survival and AML transformation. 15 Recently, several of these gene mutations were identified as specific for s-AML in comparison to de novo AML underlining their function in dysplastic differentiation since they occur already at the stage of MDS.…”
mentioning
confidence: 99%